2008
DOI: 10.1016/j.ijrobp.2008.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Trial of Bladder Filling and Three-Dimensional Dosimetry in High-Dose-Rate Vaginal Cuff Brachytherapy

Abstract: Purpose-To investigate the impact of bladder filling state on dosimetry and determine the best bladder dosimetric parameter in vaginal-cuff brachytherapy.Materials and Methods-Twenty women received vaginal cylinder high-dose-rate (HDR) brachytherapy with each fraction followed by a planning CT scan on a prospective clinical trial. The bladder was full for fraction 2 and empty for fraction 3. Dose volume histogram (DVH) and dose surface histogram (DSH) values were generated for the bladder, rectum, and urethra.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
(32 reference statements)
4
35
0
Order By: Relevance
“…Similar results were obtained by other authors. 8 They emphasized an extremely low risk rate of toxicity. Moreover, the randomized trial comparing vaginal brachytherapy alone to pelvic irradiation (PORTEC 2) published in 2010 proved that brachytherapy is effective in ensuring vaginal control and should be a treatment of choice for patients with endometrial carcinoma of high-intermediate risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by other authors. 8 They emphasized an extremely low risk rate of toxicity. Moreover, the randomized trial comparing vaginal brachytherapy alone to pelvic irradiation (PORTEC 2) published in 2010 proved that brachytherapy is effective in ensuring vaginal control and should be a treatment of choice for patients with endometrial carcinoma of high-intermediate risk.…”
Section: Discussionmentioning
confidence: 99%
“…The volume and surface area of the bladder were investigated by Stewart et al 8 They proved that D 2 cc , V50, volume of the bladder receiving 70% or more of the dose, and the surface area of bladder receiving 50% or more of the dose significantly predicted for the difference between an empty and a full bladder. The second conclusion deducted from this study was that an empty bladder did result in the nearest point of bowel being significantly closer to the vaginal vault than when bladder was full.…”
Section: Discussionmentioning
confidence: 99%
“…Several centers have reported the use of CT-based imaging for tandem and ring or ovoid (7)(8)(9)(10)(11)(12)(13)(14), interstitial (15)(16)(17)(18), or vaginal cylinder (19) cases. The use of MRI for gynecologic brachytherapy has been reported in the U.S. (16) and in Europe (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Stewart et al found that bladder filling increased the maximum bladder dose and bladder volume receiving ≥ 70% of prescription dose. Bladder filling displaced the nearest bowel away from the vaginal cylinder though [107]. Hung et al showed that bladder filling decreased small bowel dose without affecting dose to the bladder, rectum, or sigmoid colon [108].…”
Section: Vaginal Brachytherapy Treatment Deliverymentioning
confidence: 99%